Studi Fenomenologi Komunikasi Sosial Pengamen di Kota Bandung - Muhammad Fachri Rabbani Rayu Syabanayretin; Maman Suherman (UNISBA Press, 2022)
Abstract. The phenomenon of busking is one of the sosial problems in urban areas, especially in the city of Bandung and communication is the main human activity. By communicating, humans can mingle with each other. The reality of buskers is one of the sosial problems in big cities. Most people live as street singers because of poverty, but there are also many street singers who are based on their own desires and make their main capital to earn a living.The purpose of this study is to find out the motives of the busker subject in response to sosial communication,know the meaning of singing for the subject and to find out the communication experience of research subjects in response to sosial communication.This researcher uses a qualitative method with a phenomenological study approach. The technique of collecting data was carried out by in-depth interviews, observations, and documentation. The result of this research is that the subject's motives for becoming buskers in the Bandung City area are divided into 4 categories, namely economic motives, hobby motives, learning motives, and own desire motives. This motive is also an impulse from oneself that is caused by the needs that he wants to fulfill himself or the needs of his family. The meaning of the group’s musicians is divided into 3, namely homogeneous, partial, and artificial, so the meaning of busking for research subjects is as individuals who have responsibilities to themselves and their families, individuals who try to get rid of dependence, and individuals who always try to have social relations on the streets. The research subject's experience of social communication in responding to social communication is twofold. namely social communication that takes place in the form of individual communication to other music singers and social communication that takes place in the form of individual communication to parents and siblings. Abstrak. Fenomena pengamen merupakan salah satu masalah sosial di perkotaan khusus nya di kota Bandung dan Komunikasi adalah aktivitas pokok manusia. Dengan berkomunikasi manusia bisa saling berbaur. Realita pengamen yakni salah satu masalah sosial di kota-kota besar. Kebanyakan orang hidup sebagai pengamen di karenakan oleh kemiskinan, akan tetapi banyak juga pengamen yang didasari oleh keinginan sendiri dan di jadikan modal utama ia mencari nafkah. Tujuan dari penelitian ini ingin mengetahui motif subjek pengamen dalam menanggapi komunikasi sosial, mengetahui makna mengamen bagi subjek dan untuk mengetahui pengalaman komunikasi subjek penelitian dalam menanggapi komunikasi sosial. Peneliti ini menggunakan metode kualitatif dengan pendekatan studi fenomenologi. Teknik pengumpulan data yang dilakukan dengan wawancara mendalam, observasi, dan dokumentasi. Hasil dari penelitian ini adalah motif subjek menjadi pengamen di wilayah Kota Bandung di bagi menjadi 4 kategori, yaitu motif ekonomi, motif hobi, motif keinginan belajar, dan motif keinginan sendiri. Motif ini juga merupakan dorongan dari diri sendiri yang di timbulkan karena kebutuhan yang ingin dipenuhi oleh dirinya sendiri atau kebutuhan keluarga. Makna kelompok pemusik terbagi menjadi 3, yaitu makna homogen, makna parsial, dan makna artifisial, jadi makna pengamen subjek penelitian adalah sebagai individu yang mempunyai tanggung jawab pada diri nya sendiri dan keluarganya, individu yang berusaha untuk melepaskan ketergantungan, dan individu yang selalu berusaha memiliki relasi sosial dalam di jalanan. Pengalaman komunikasi sosial subjek penelitian dalam menanggapi komunikasi sosial ada dua. yaitu komunikasi sosial yang berlangsung dalam bentuk komunikasi individual terhadap pengamen musik lainnya dan komunikasi sosal yang berlangsung dalam bentuk komunikasi individual terhadap orang tua dan saudara.